2004
DOI: 10.1021/jp036387k
|View full text |Cite
|
Sign up to set email alerts
|

Heat of Adsorption of Butane on Multiwalled Carbon Nanotubes

Abstract: We report the isosteric heats of adsorption, q st , for butane on multiwalled carbon nanotubes (MWNTs) over a range of surface loadings at temperatures below the normal boiling point. Butane is a nonspherical, nonpolar molecule that may exhibit different orientations in multilayer adsorption. The morphology of our MWNTs is such that only surface adsorption or capillary condensation can occur: no interstitial sites between nanotubes are available to butane. For these nanotubes, exterior surface adsorption is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…On the other hand, Gotovac et al (2007) find that the external surface of SWNTs is the main area for naphthalene adsorption, but the inner pore sites are not due to the dimensional restriction. The reason for the unavailable interstitial sites is that the organic molecules are too large to fit into this area (Hilding and Grulke, 2004). EPI molecular structure is relatively larger, thus, we infer that external surface area is the most important factor dominating EPI adsorption on CNTs.…”
Section: Adsorption Isothermmentioning
confidence: 92%
“…On the other hand, Gotovac et al (2007) find that the external surface of SWNTs is the main area for naphthalene adsorption, but the inner pore sites are not due to the dimensional restriction. The reason for the unavailable interstitial sites is that the organic molecules are too large to fit into this area (Hilding and Grulke, 2004). EPI molecular structure is relatively larger, thus, we infer that external surface area is the most important factor dominating EPI adsorption on CNTs.…”
Section: Adsorption Isothermmentioning
confidence: 92%
“…In graphene-based materials, each defect has certain mobility parallel to the graphene plane. Several studies have indicated that defective sites are of great importance to the adsorption process [41][42][43][44][45][46]. The presence of these defects in the structure creates highly reactive sites for the adsorption of various species.…”
Section: Presence Of Defectsmentioning
confidence: 99%
“…The second and subsequent layers may not necessarily be considered as condensation, as such a state has been reported to occur only after 2.5 monolayers for butane on multiwalled carbon nanotubes (which have lower initial heats of adsorption than sulfated zirconia). [64] …”
Section: Interpretation Of Isobarsmentioning
confidence: 99%